The Impact of Digital Services in Promoting Financial Inclusion: An Analytical Study Using Panel Data Regression in Iraq (International Journal of Financial, Administrative and Economic Sciences, 2026)
Results: Overall, the results are promising, with clear statistical evidence indicating the importance of a financial inclusion approach that leverages digital innovations while addressing various economic factors and demographic needs.Purpose: This paper aims to understand the complex relationship between digital financial services (DFS) and digital payment methods to promote financial inclusion. A more holistic view is needed to provide cost-effective and efficient alternatives to traditional banking services, thereby facilitating increased economic growth.Gap: This study contributes to bridging the gap with an approach that ensures a fairer, more accessible, and more efficient financial payment system to promote financial inclusion and societal well-being.Importance: The findings of this paper will be economically valuable to financial institutions and emerging digital technology companies that deal with financial payment services, to individuals who use payment processes, and to other researchers seeking continuous adaptation and improvement.Impact: This has provided a better understanding of the competition between digital and traditional payment methods, indicating their continued long-term importance. This underscores the need for strategies tailored to diverse population segments.Methodology: The analysis relied on data obtained from the Central Bank of Iraq's website, which provided reports and statistics related to digital payments and financial inclusion, covering the period from 2017 to 2024.
Keywords: Digital Payments; Financial Inclusion; Digital Payment Methods; Digital Financial Services; Economic Growth